2020
DOI: 10.1007/s00268-020-05406-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hepatic Artery Variations and Reconstructions on the Outcome of Orthotopic Liver Transplantation

Abstract: Background Donor variational arteries often require complex reconstruction. Methods We analysed the incidence of different variations, types of arterial reconstructions and their impact on postoperative results from 409 patients undergoing liver transplantation at Karolinska Institute between 2007 and 2015. Results A total of 292 (71.4%) liver grafts had a standard hepatic artery (SHA), and 117 (28.6%) showed hepatic artery variants (HAV). 58% of HAV needed reconstruction. The main variations were variant left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 32 publications
1
21
0
2
Order By: Relevance
“…12 with the results of the present study where the variations of the left hepatic artery were more than the right hepatic artery. 23 In the present study the incidence of replaced RHA (Type 3) was observed in 9.5% and the accessory RHA was observed in 4% cases. The type 3 that is an accessory/replaced RHA is of most important type as it always requires an arterial reconstruction.…”
Section: Discussionsupporting
confidence: 52%
“…12 with the results of the present study where the variations of the left hepatic artery were more than the right hepatic artery. 23 In the present study the incidence of replaced RHA (Type 3) was observed in 9.5% and the accessory RHA was observed in 4% cases. The type 3 that is an accessory/replaced RHA is of most important type as it always requires an arterial reconstruction.…”
Section: Discussionsupporting
confidence: 52%
“…Cold and warm ischemia time were defined as the time interval between cross‐clamp and graft placement into the recipient abdomen, and between graft placement into the recipient abdomen and portal declamping, respectively. In accordance with previous reports, [ 1,2 ] the arterial ischemia time was defined as the time interval between portal declamping and completion of arterial reconstruction.…”
Section: Methodsmentioning
confidence: 90%
“…Pacientes com TAH têm taxas de mortalidade entre 27-58%, e quando o retransplante não é realizado, essa taxa cresce para cerca de 73%. 15,16 De acordo com o período em que a TAH ocorre após o transplante, ela pode ser classificada precoce ou tardia, sendo estabelecido como parâmetro o intervalo de um mês antes ou depois da cirurgia, respectivamente. No entanto, esse período que divide a TAH precoce da tardia ainda varia na literatura.…”
Section: Resultsunclassified
“…6,8,17 Condições como aterosclerose e alterações na túnica íntima mantêm relação com a idade do paciente e com comorbidades como a hipertensão ou diabetes mellitus e, por isso, é de extrema importância o conhecimento desses fatores para uma efetiva execução da reconstrução arterial. 8,14,16,17 que a sutura foi colocada corretamente através de todas as camadas arteriais, e que não há envolvimento da parede posterior durante a sutura da parede anterior. Além disso, é preciso também minimizar a incidência da dissecção da túnica íntima, realizando cuidadosa dissecção e preparação da artéria receptora, afim de evitar problemas importantes como a embolização.…”
Section: Resultsunclassified